Surgical Procedure Characteristics and Risk of Sharps-Related Blood and Body Fluid Exposure. (5th October 2015) - Myers, Douglas J.; Lipscomb, Hester J.; Epling, Carol; Hunt, Debra; Richardson, William; Smith-Lovin, Lynn; Dement, John M.
Abstract : OBJECTIVE: To use a unique multicomponent administrative data set assembled at a large academic teaching hospital to examine the risk of percutaneous blood and body fluid (BBF) exposures occurring in operating rooms. DESIGN: A 10-year retrospective cohort design. SETTING: A single large academic teaching hospital. PARTICIPANTS: All surgical procedures (n=333, 073) performed in 2001–2010 as well as 2, 113 reported BBF exposures were analyzed. METHODS: Crude exposure rates were calculated; Poisson regression was used to analyze risk factors and account for procedure duration. BBF exposures involving suture needles were examined separately from those involving other device types to examine possible differences in risk factors. RESULTS: The overall rate of reported BBF exposures was 6.3 per 1, 000 surgical procedures (2.9 per 1, 000 surgical hours). BBF exposure rates increased with estimated patient blood loss (17.7 exposures per 1, 000 procedures with 501–1, 000 cc blood loss and 26.4 exposures per 1, 000 procedures with >1, 000 cc blood loss), number of personnel working in the surgical field during the procedure (34.4 exposures per 1, 000 procedures having ≥15 personnel ever in the field), and procedure duration (14.3 exposures per 1, 000 procedures lasting 4 to <6 hours, 27.1 exposures per 1, 000 procedures lasting ≥6 hours). Regression results showed associations were generally stronger for suture needle–related exposures. CONCLUSIONS: Results largely support other studies found in the literature. However, additional research should investigate differences in risk factors for BBF exposures associated with suture needles and those associated with all other device types. Infect. Control Hosp. Epidemiol. 2015;37(1):80–87